ENGLISH LEARNING GRAMMAR STRATEGIES : ACHIEVEMENT, OBSTACLES, AND SOLUTION - Syafryadin Syafryadin; Iis Sujarwati; Dedi Sofyan (STKIP Siliwangi, 2022)
English learning grammar strategies can be an issue that students and lecturers face in the university. This study aimed to find out the students’ achievement, obstacles and solution in learning grammar by using English grammar strategies. Mixed method was employed to gain the research objectives. Thirty three students were selected as the respondents of this research. The intruments were grammar test and interview. The data were analyzed by using descriptive statistics for quantitative data and qualitative data were analyzed by using qualitative analysis with several steps, such as data reduction, display and conclusion for qualitative data. The results showed that students got enhancement in terms of their grammar ability. It can be proved by looking at their pretest and postest. Moreover, students faced obstacles in implementing grammar strategies namely poor understanding about grammar, difficult to memorize the rules, grammar anxiety, seldom to work in group, and time limitation. The possible solution can be extra lesson from the lecturer or discussing with their friends, more practice in grammar, giving reinforcement and motivation, working in group, and be smart in managing time for learning grammar.